ETIKA DALAM KEGIATAN KEMASYARAKATAN: DENGAN KEGIATAN BERBAGI NASI - Wahyu Nugraha (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Business ethics in a societal context refers to a company's moral behavior that takes into account its impact on society as a whole. In the era of globalization and increasingly close connectivity, companies have a responsibility not only to achieve economic profits, but also to pay attention to their contribution to social welfare. This abstract discusses the implications and challenges of business ethics in society, highlighting the role of companies as active members in shaping and supporting the sustainability of society. The implications of business ethics in society include the obligation of companies to ensure that their operational activities comply with moral norms and that their contribution to society is more than just creating financial gain. Society-centered business ethics requires companies to pay attention to their impact on the environment, human rights, and social justice. The challenges facing business ethics in society involve frequent conflicts between corporate profits and the general welfare. Economic globalization can create increasing inequality, and companies are faced with pressure to meet shareholder demands while maintaining ethical integrity. Managing this balance requires business policies and practices that focus on transparency, accountability and sustainable development. Thus, this research underlines the need for a paradigm shift in the view of business, where business ethics is not only understood as a moral obligation, but also as a foundation for growth sustainable and inclusive economy in society.